On the use of temporal filtering for mitigating galactic synchrotron calibration bias in 21 cm reionization observations. Issue 1 (7th April 2023) - Charles, Ntsikelelo; Kern, Nicholas; Bernardi, Gianni; Bester, Landman; Smirnov, Oleg; Fagnoni, Nicolas; Acedo, Eloy de Lera
ABSTRACT: Precision antenna calibration is required for mitigating the impact of foreground contamination in 21 cm cosmological radio surveys. One widely studied source of error is the effect of missing point sources in the calibration sky model; however, poorly understood diffuse galactic emission also creates a calibration bias that can complicate the clean separation of foregrounds from the 21 cm signal. In this work, we present a technique for suppressing this bias with temporal filtering of radio interferometric visibilities observed in a drift-scan mode. We demonstrate this technique on mock simulations of the Hydrogen Epoch of Reionization Array (HERA) experiment. Inspecting the recovered calibration solutions, we find that our technique reduces spurious errors by over an order of magnitude. This improved accuracy approaches the required accuracy needed to make a fiducial detection of the 21 cm signal with HERA, but is dependent on a number of external factors that we discuss. We also explore different types of temporal filtering techniques and discuss their relative performance and trade-offs.